The Role and Contribution of The New Institutional Economics In Economic System Performance - Agus Arwani; Unggul Priyadi (Jurnal Simki Economic, 2024)
This study investigates new institutions' contributions and economic implications in current economic developments. This study uses a qualitative approach with a literature study method. The study illustrates key thought concepts and relevant works from figures such as Douglass North, Elinor Ostrom, Oliver Williamson, Ronald Coase, and Avner Greif through analysis of various reference sources, including books, journal articles, and other related publications. The results of the literature study show that New Institutional Economics has an essential contribution to understanding the role of formal and informal institutions in shaping economic behavior and Performance. Legal institutions, such as laws, regulations, and public policies, provide the framework for economic interactions, literature study results whereas informal institutions, such as norms, beliefs, and social networks, influence individual economic decisions. The importance of institutions and organizations in improving economic efficiency and overcoming problems arising in the economic system is also highlighted in this study. In the context of New Institutional Economics, institutions and organizations act as mechanisms for reducing transaction costs, resolving conflicts, and increasing trust and cooperation among economic actors. Its theoretical implications strengthen an understanding of how institutions and organizations can shape economic behavior and Performance. In contrast, its practical implications can provide direction for more relevant and effective public policies addressing economic and social problems.